2021
DOI: 10.1186/s12970-021-00421-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different doses of caffeine on maximal strength and strength‐endurance in women habituated to caffeine

Abstract: Purpose The main goal of this study was to assess the acute effects of 3 and 6 mg of caffeine intake per kg of body mass (b.m.) on maximal strength and strength-endurance in women habituated to caffeine. Methods Twenty-one healthy resistance-trained female students (23.0 ± 0.9 years, body mass: 59.0 ± 6.6 kg), with a daily caffeine intake of 5.8 ± 2.6 mg/kg/b.m. participated in a randomized, crossover, double-blind design. Each participant perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 56 publications
2
59
1
2
Order By: Relevance
“…After reading 30 full-text papers, 7 studies were found that satisfied the inclusion criteria [ 7 , 10 , 11 , 15 , 16 , 17 , 18 ]. In the secondary search, there were 669 search results, and one study was additionally included [ 19 ]. Therefore, we included a total of 8 studies in the present review [ 7 , 10 , 11 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After reading 30 full-text papers, 7 studies were found that satisfied the inclusion criteria [ 7 , 10 , 11 , 15 , 16 , 17 , 18 ]. In the secondary search, there were 669 search results, and one study was additionally included [ 19 ]. Therefore, we included a total of 8 studies in the present review [ 7 , 10 , 11 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the secondary search, there were 669 search results, and one study was additionally included [ 19 ]. Therefore, we included a total of 8 studies in the present review [ 7 , 10 , 11 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations